Uma análise de implantação de projetos de automação residencial no mercado de São Luis-MA - FEITOSA, Manoel Evandro de Carvalho (2022)
Home automation is a booming market in the world. This technology is already found with relative frequency in many cities applied in commercial, industrial and service buildings. However, it is still little implemented in private homes, despite the benefits that an automated house presents, such as increased comfort, autonomy and safety for users and having an installation cost of approximately R$ 5,000.00, which is accessible to the upper classes. A, B and C. This is due to the lack of more specific information on the subject and the existence of a wide variety of communication protocols that are incompatible, which makes the home automation market advance more slowly. The future of home automation undoubtedly involves the popularization of the use of wireless systems, reducing costs with installation and launching of cables, increasing the portability of its components, in addition to the advent of 5G technology that will allow a universe of possibilities. In this context, this work seeks to generally propose a roadmap for the implementation of home automation projects, through the presentation of systems/routines that can be automated, the evaluation of devices available in the local market (São Luís - MA), the analysis of the infrastructure necessary for the installation of a home automation project and the presentation of installation costs to the final consumer. This work contributes to the review of smart home projects operating as successful laboratories around the world, presenting the main communication protocols in home automation available on the market, discussion of the variety of processes in a house that can be automated, analysis of which the best software option available on the market to control a home automation system, presentation of the main technologies available on the market for smart homes in the local market and implementation of a project in a residence as a case study. With this, this work seeks to be useful in helping the elaboration of home automation projects, contributing with information about communication protocols, management and control software, systems that can be automated and devices that are available in the market.